PROSES INTERNALISASI NILAI-NILAI AGAMA ISLAM DALAM MEMBENTUK PERILAKU SOSIAL KEAGAMAAN SANTRI - Panjalu, Anggi Prakas Eka; Hakimah, Bintang Sunny; Khotimah, Siti Kusnul; Fuadi, Imam (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
This research was motivated by the decline in social manners and moral ethics in association, which led to the emergence of a number of negative effects in the community. The method in this study uses a qualitative approach and the type of research is a multi-site study. Data collection techniques using observation, interviews and documentation. The results of this study indicate (1) the process of internalizing Islamic religious values through several stages, namely providing information to students, then establishing two-way communication to provide values to students, and students understanding Islamic religious values and then implementing them in the form of social behavior according to with understanding and examples seen. (2) the method of internalizing Islamic religious values in shaping the socio-religious behavior of students, including recitation, exemplary, and habituation. (3) the result of internalizing Islamic religious values in shaping the socio-religious behavior of santri is the formation of social behavior that is in accordance with Islamic religious values, such as courtesy, humility, brotherhood, independence and friendship. Keywords: Internalization, Islamic Religious Values, Religious Social Behavior